The effects of different levels of L-carnitine and fat on performance and egg quality of laying hens - Rezaei, Masour; Dehghani, Samaneh; AliGhaffari, Jan; Haghnazar, Alizera (MTT Agrifood Research Finland, 2008)
L-carnitine is used as feed additive in poultry diets to increase yield and to improve feed efficiency. The major role of L-carnitine appears to be the transport of long-chain fatty acids into mitochondria for À oxidation. This experiment was carried out to determine the effects of two levels of fat (10 and 30 g kg-1 DM) and two levels of L-carnitine (0 and 250 mg kg-1) on performance, egg quality, and blood parameters of laying hens in a factorial arrangement (2 ~2) with completely randomized design with six replicates and four laying hens in each replicate. During the experiment feed intake, egg weight, egg production, feed conversion ratio, and some blood parameters (triglyceride, cholesterol, LDL, HDL), egg quality (albumen height, egg shell thickness, egg shell breaking strength), and cholesterol content of eggs were measured. Results of this experiment indicated that supplementation of L-carnitine in laying hens diets had not significant effect on performance, cholesterol content of eggs, but decreased the levels of triglyceride, cholesterol, LDL in blood serum and increased albumen height of eggs significantly (p<0.05). Supplementation of fat significantly increased feed intake and egg weight (p<0.05), but had not significant effect on blood parameters, egg quality and cholesterol content of eggs.
Keywords: Ko; L-carnitine; fat; egg quality; cholesterol; laying hens